ANALISIS WACANA HIDUP MATI LISTRIK PADA PROGRAM TALK SHOW MATA NAJWA DI STASIUN TV TRANS 7 - Pratama, Yogi; Abidin, Sholihul (SCIENTIA JOURNAL, 2020)
Critical Discourse Analysis is always interesting to study more deeply. The power of the media and public perception that makes critical discourse research continue to grow. The formulation of the problem in this research is how is the analysis of the critical discourse of Van Djik's model in the Mata Najwa program episode "Living Off Electricity"? This study aims to describe the critical discourse analysis of the Van Djik model constructed by Najwa Sihab as the master of ceremonies in the Mata Najwa program. The data analysis technique uses documentation and observation techniques. The theory used is the critical discourse analysis of Van Djik's model. The results and discussion of this study indicate: (1). Shihab uses language in a structured way to guide shows based on topics, microstructure, Super Structures, and Micro Structure in order to provide information to the listener or viewers in understanding talk shows on all episodes: (2). social cognition found in all episodes, Shihab tries to maintain and present the program to keep it warm and the atmosphere alive and interesting to watch, as well as facilitate the needs of viewers in understanding the Mata Najwa talk show on Trans7: (3). the social context contained in all episodes of the Mata Najwa talk show, Indonesian Shihab serves to support the clarity of meaning about the material being discussed and try to dig up information through questions posed to the speakers